2016
DOI: 10.1245/s10434-015-5063-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Percent Myxoid Component to Predict Outcome in High-Grade Myxofibrosarcoma and Undifferentiated Pleomorphic Sarcoma

Abstract: Background-Myxofibrosarcoma and undifferentiated pleomorphic sarcoma (UPS) are aggressive, genetically complex sarcomas. The minimum myxoid component used as a criterion for myxofibrosarcoma varies widely, so we determined the optimal myxoid component cutpoints for stratifying outcomes of UPS and myxofibrosarcoma. We also analyzed clinicopathologic factors associated with outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…1B) (p=0.021). To further test the importance of this grouping, we performed a multivariate analysis adjusting for tumor size, the most important known clinical predictor in myxofibrosarcoma (4, 2325). Both variables were independent predictors of DSS: tumor size as a continuous variable had a hazard ratio of 1.15 (p=0.010) and cluster 1 vs cluster 2 membership had a hazard ratio of 5.26 (p=0.014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) (p=0.021). To further test the importance of this grouping, we performed a multivariate analysis adjusting for tumor size, the most important known clinical predictor in myxofibrosarcoma (4, 2325). Both variables were independent predictors of DSS: tumor size as a continuous variable had a hazard ratio of 1.15 (p=0.010) and cluster 1 vs cluster 2 membership had a hazard ratio of 5.26 (p=0.014).…”
Section: Resultsmentioning
confidence: 99%
“…Formerly known as a myxoid variant of malignant fibrous histiocytoma (a classification representing undifferentiated pleomorphic sarcomas), myxofibrosarcoma is currently regarded as a distinct fibroblastic/myofibroblastic tumor type defined by cellular pleomorphism, a curvilinear vascular pattern, and a myxoid stromal component (1–3). While the mainstay of therapy is surgical resection, and 5-year disease-specific survival (DSS) after surgery for primary high-grade myxofibrosarcoma is 60–70%, approximately 30–40% of high-grade tumors metastasize to lung, bone, or lymph nodes (4–7). Once myxofibrosarcoma has metastasized, conventional chemotherapy and radiation therapy are largely palliative, and metastasis eventually leads to disease-related death.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, malignancies, which were rich in mucous matrix, usually exhibited insufficient glucose transporter expression and showed low FDG uptake [ 34 ]. In addition, a study by Lee AY, et al showed that myxofibrosarcomas with a higher proportion of mucus are associated with a better prognosis [ 35 ]. Therefore, we speculate that this is the reason why the PET/CT imaging features of these tumors tend to be benign ones.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG is an analog of glucose and previous studies claimed that lesions with abundant in ltration of in ammatory cells or ones containing giant cells can display upregulation of hexokinase-2, leading to high FDG a nity [34]. Conversely, malignancies, which were rich in mucous matrix, usually exhibited insu cient glucose transporter expression and showed low FDG uptake [35].In addition, a study by Lee AY, et al showed that myxo brosarcomas with a higher proportion of mucus are associated with a better prognosis [36]. Therefore, we speculate that this is the reason why the PET/CT imaging features of these tumors tend to be benign ones.…”
Section: Discussionmentioning
confidence: 97%